Leader-Member Exchange and Its Impact on Employee Innovative Work Behavior: An Analysis of Nepalese IT Sector - Saud, Jagdish (Brixton Scholarly Review, 2025)
In today's fast-paced and highly competitive markets, companies must prioritize innovation to remain competitive. In this context, leadership plays a pivotal role, as leaders are responsible for fostering an environment that encourages employee creativity and innovation. This study investigates the impact of Leader-Member Exchange (LMX) dimensions, as well as the overall quality of LMX, on employees' innovative work behavior. A descriptive research design was employed, utilizing online survey responses from 263 employees in the IT sector of the Kathmandu Valley. Descriptive statistics and structural equation modeling were applied to analyze the data. The findings revealed a moderate level of LMX quality within the IT sector. Furthermore, overall LMX quality was found to have a significant positive effect on employees' innovative work behavior. Among the four dimensions of LMX, loyalty and professional respect were identified as having a significant positive influence on innovative behavior, while affect and contribution had no significant impact. Based on these results, it is recommended that organizations invest in LMX training and carefully select leaders with this leadership style to enhance and foster employee innovation.